2020
DOI: 10.1155/2020/9192757
|View full text |Cite
|
Sign up to set email alerts
|

Research on Carbonation Characteristics and Frost Resistance of Iron Tailings Powder Concrete under Low‐Cement Clinker System

Abstract: The accelerated carbonation, natural carbonation, fast freeze-thaw test, and pore structure analysis of C30 and C50 concrete with different proportions of iron tailings powder and slag powder were tested, respectively. The results show that the accelerated carbonation depth and natural carbonation depth of concrete increase with the increase of iron tailings powder content. The prediction model of carbonation depth of iron tailings powder concrete is established by introducing the iron tailings content coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Wu et al [7] established predictive modeling for the depth of carbonation of iron tailings powder concrete by introducing various influential factors. The carbonation process is very complex and is influenced by many factors, and there is interaction between biochemical factors, such as fungi and mildew; these factors affect the carbonation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [7] established predictive modeling for the depth of carbonation of iron tailings powder concrete by introducing various influential factors. The carbonation process is very complex and is influenced by many factors, and there is interaction between biochemical factors, such as fungi and mildew; these factors affect the carbonation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of beneficiation technology, tailings have become finer and finer. The stock of fine-grained tailings below 75 μm accumulates rapidly (Wu et al, 2020). Fine-grained tailings will cause a series of problems such as filling rheology and high cost Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al, studied the effect of iron tailing powder and slag powder composite admixture on the performance of concrete and found that iron tailing can partially replace mineral powder as concrete admixture, which is conducive to improving the compatibility [ 12 ]. Wu et al, studied the effect of a composite admixture of iron tailing powder and slag powder on the frost resistance of concrete and found that iron tailing can optimize the pore structure of concrete and improve the frost resistance [ 13 ]. Han et al, studied the effect of iron tailings on the performance of fly ash concrete and found that iron tailings are beneficial to improving the early strength of concrete but reduce the later strength and improve the durability of concrete [ 14 ].…”
Section: Introductionmentioning
confidence: 99%